Structural analysis of mycolic acids from phenol-degrading strain of Rhodococcus erythropolis by liquid chromatography-tandem mass spectrometry - Kolouchová, Irena; Schreiberová, Olga; Masák, Jan; Sigler, Karel; Rezanka, Tomáš (Folia microbiologica, 2012)
We used reversed phase liquid chromatography-electrospray ionization tandem mass spectrometry for direct analysis of mycolic acids (MAs) from four different cultivations of Rhodococcus erythropolis. This technique enabled us to identify and quantify the specific molecular species of MAs directly from lipid extracts of the bacterium, including the determination of their basic characteristics such as retention time and mass spectra. We identified a total of 60 molecular species of MAs by means of LC/MS. In collision-induced dissociation tandem mass spectrometry, the [M-H](-) ions eliminated two residues, i.e., meroaldehyde and carboxylate anions containing α-alkyl chains. The structural information from these fragment ions affords structural assignment of the mycolic acids, including the lengths and number of double bond(s). Two strains, i.e., R. erythropolis CCM 2595 and genetically modified strain CCM 2595 pSRK 21 phe were cultivated on two different substrates (phenol and phenol with addition of humic acids as a sole carbon source). The addition of humic acids showed that there is a marked increase of unsaturated mycolic acids, mostly in the range of 20-100 %. This effect is more pronounced in the R. erythropolis CCM 2595 strain.
Keywords: fenol; Humic Substances; Phenol; huminové látky; Biotransformation; Rhodococcus; kyseliny mykolové; tandemová hmotnostní spektrometrie; kultivační média; uhlík; Carbon; Chromatography, Liquid; biotransformace; chromatografie kapalinová; Culture Media; Mycolic Acids; Tandem Mass Spectrometry